Clinical pharmacology at the core of translational science - Waldman, Scott A (Expert Rev Clin Pharmacol, 2011)
“Convergence of national interests in advancing molecular therapeutics into practice with core competencies in clinical pharmacology represents a unique opportunity to elevate the visibility of this pioneering discipline as part of the foundation of clinical and translational science.”